Revolutionizing Payment Systems: The Integration of TRAM and Trust in QRIS Adoption for Micro, Small, and Medium Enterprises in Indonesia - Adisthy Shabrina Nurqamarani; Sarah Fadilla; Ari Juliana (Journal of Information Systems Engineering and Business Intelligence)
Background: In an era where digital finance is growing rapidly, the Quick Response Code Indonesian Standard (QRIS) revolutionizes the payment system through a single unifying code. This study brings novelty in integrating TRAM and Trust in the adoption of QRIS in micro, small, and medium enterprises (MSMEs) in Indonesia, for which studies are still limited.